Effects of Arctic sea-ice concentration on surface radiative fluxes in four atmospheric reanalyses - T. Uhlíková; T. Uhlíková; T. Vihma; A. Y. Karpechko; P. Uotila (The Cryosphere)
Spatiotemporal variations and climatological trends in the sea-ice concentration (SIC) are highly important for the energy budget of the lower atmosphere and the upper ocean in the Arctic. To better understand the local, regional, and global impacts of the recent rapid sea-ice decline, one of the key issues is to quantify the interactions of SIC and the surface radiative fluxes. We analyse these effects utilizing four global atmospheric reanalyses – ERA5, JRA-55, MERRA-2, and NCEP/CFSR – and evaluate the uncertainties arising from inter-reanalysis differences in the sensitivity of the surface radiative fluxes to SIC. Using daily data over the period 1980–2021, the linear orthogonal distance regression indicates similar sensitivity of surface upward longwave radiation to SIC in all reanalyses with the greatest sensitivity in the cold season November–April (over 150 W m−2 per −0.1 change in SIC) and up to 80 W m−2 per −0.1 change in SIC in May–October. We find that the effect of SIC on surface upward longwave and shortwave radiation has mostly weakened in all seasons between the study periods of 1980–2000 and 2001–2021. The decrease in the sensitivity of upward longwave radiation to SIC can be attributed to the increasing surface temperature of sea ice, which dominated in the inner ice pack, and to the sea-ice decline, which dominated in the marginal ice zone. Approximately 80 % of the decadal decrease in upward shortwave radiation in May–July was caused by a decrease in surface albedo controlled by SIC decrease, and the rest was caused by a decrease in downward shortwave radiation due to the increase in cloudiness that was mostly close to sea-ice margins.